The third dimension: a novel set‐up for filming coelacanths in their natural environment. Issue 3 (7th November 2016) - Décamps, Thierry; Herrel, Anthony; Ballesta, Laurent; Holon, Florian; Rauby, Thibault; Gentil, Yannick; Gentil, Cédric; Dutel, Hugo; Debruyne, Régis; Charrassin, Jean‐Benoit; Eveillard, Guillaume; Clément, Gaël; et al.
Summary: Here, we describe a novel design to obtain three‐dimensional data on the movements of aquatic organisms at depths of up to 140 m. The set‐up consists of two synchronized high‐speed cameras fixed to two articulated arms. The set‐up was successfully used to film and quantify the locomotion of coelacanths Latimeria chalumnae living at a depth of about 120 m in Sodwana Bay, South Africa. As an example, the detailed motion of the dorsal fin is presented here. This set‐up can be used for any underwater applications that require synchronized video recordings of medium‐ to large‐sized animals.